Genomic diversity and intragenic recombination of species C rotaviruses - Oki, Hisako; Masuda, Tsuneyuki; Hayashi-Miyamoto, Michiko; Kawai, Megumi; Ito, Mika; Madarame, Hiroo; Fukase, Yuka; Takemae, Hitoshi; Sakaguchi, Shoichi; Furuya, Tetsuya; Mizutani, Tetsuya; Oba, Mami; et al. (Journal of general virology, 2022)
Rotavirus C (RVC) is a major cause of diarrhoea in swine, cattle, and humans worldwide. RVC exhibits sequence diversity in all 11 genes, especially in VP4 and VP7, and all segment-based genotyping has been performed similar to rotavirus A. To date, recombination events have been reported in rotavirus A and B. However, there are no reports describing gene recombination of RVC, except for recombination in NSP3 between RVC and rotavirus H. In this study, nine porcine RVC strains identified in Japanese pigs were completely sequenced and analysed together with RVC sequences from the GenBank database. The analyses showed that sequences of the VP4, VP2, and NSP1 of several porcine RVC strains did not branch with any of those of the RVC strains in the GenBank database, suggesting new genotypes. Several homologous recombination events, between or within genotypes, were identified in the VP4, VP7, VP2, NSP1, and NSP3 genes. Of these, nine, one, and one intergenotypic recombination events in the VP4, VP2, and NSP3 genes, respectively, were supported with sufficient statistical values. Although these findings suggest occurrences of the intragenic recombination events in the RVC genome, potential sequence errors and poor sequence assemblies in the databases should be watched with care. The results in this study present data about the important recombination events of the RVCs, which influence evolution of the virus by aiding them to gain genetic diversity and plasticity, although further sequence data will be necessary to obtain more comprehensive understanding of such mechanisms.